Historical analysis on information and knowledge society - Díaz Bernal, Juan Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2012)
This reflection article shows a general perspective of the society cotemporary man is immersed in. On the one hand, it was used a historical methodology in order to provide a global perspective of the different studied facts throughout time, on the other hand, a descriptive one was applied in order to give an answer to the effects in the post capitalist society. The analysis carried out demonstrates the importance of work within education and pedagogy in the XXI century as well as its consequences. Such effects affect knowledge in, at least, three stages: genealogically, where reflection origins take shape, another one, when showing the innovations of society which is highly influenced by global capitalistic technology, and finally, when displaying the changes that happen in society. As a conclusion, it is answered the question: ‘Is the information society a knowledge society?’